2017
DOI: 10.1177/0042098017712832
|View full text |Cite
|
Sign up to set email alerts
|

Tenure change in London’s suburbs: Spreading gentrification or suburban upscaling?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Buy-to-let purchases may trigger social and ethnic neighborhood change, exacerbating disparities between neighborhoods (Paccoud, 2017;Paccoud et al, 2020;Van Criekingen, 2010). Other studies, however, highlight how both private individuals and large-scale investors have turned to investing in single-family dwellings in the suburbs of major cities (Fields, 2018;Mills et al, 2019;Paccoud & Mace, 2018). Non-conventional forms of private landlordism, e.g., AirBnB remain overwhelmingly concentrated in central neighborhoods of popular cities (Cocola-Gant & Gago, 2019;Wachsmuth & Weisler, 2018).…”
Section: Socio-spatial Dynamicsmentioning
confidence: 99%
“…Buy-to-let purchases may trigger social and ethnic neighborhood change, exacerbating disparities between neighborhoods (Paccoud, 2017;Paccoud et al, 2020;Van Criekingen, 2010). Other studies, however, highlight how both private individuals and large-scale investors have turned to investing in single-family dwellings in the suburbs of major cities (Fields, 2018;Mills et al, 2019;Paccoud & Mace, 2018). Non-conventional forms of private landlordism, e.g., AirBnB remain overwhelmingly concentrated in central neighborhoods of popular cities (Cocola-Gant & Gago, 2019;Wachsmuth & Weisler, 2018).…”
Section: Socio-spatial Dynamicsmentioning
confidence: 99%
“…Therefore, no claims are made for the possibility of generalising the findings to other groups. While the shift to middleclass renting in London's suburbs represents a significant social change (Paccoud & Mace 2018), the sample represents established owner-occupiers not directly subject to emerging middle class uncertainty linked to the inability to access owner-occupation (Benson & Jackson 2017), although this may be a concern for their children. Rather, following Yin (2009), the case studies raise points that might be tested elsewhere, including with a different age profile and in different suburbs.…”
Section: <Insert Figure 1 About Here 'Map Of London Boroughs (Outer London In Light Grey) With Approximate Location Of Case Studies Pinnementioning
confidence: 99%
“…In the case of the United Kingdom, Paccoud (2017) showed that the deregulation of the Private Rented Sector since 1988 enabled the spread of buy-to-let gentrification in more central, disadvantaged and urban areas of England than gentrification linked to increases in ownership. In London, Paccoud and Mace (2018) found that this pushed buy-to-let gentrification into suburban locations that had remained immune to previous rounds of gentrification.…”
Section: Introductionmentioning
confidence: 99%
“…This article is a development of the study of two types of gentrification described in Paccoud (2017) and Paccoud and Mace (2018). Therefore, in the rest of this section, we provide an outline of the general method before, in the next section, turning to the ethnic dimension that is the subject of this article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation